Chitosan in the induction of resistance to the damping off tomato seedlings caused by Rhizoctonia solani Kuhn - Rocha, Rita de Cassia Dosciatti Serrão; Mazaro, Sérgio Miguel; Possenti, Jean Carlo; Freddo, Álvaro Rodrigo; Zorzzi, Ivan Carlos; Dallacosta, Nean Locatelli (Scientia Agraria Paranaensis, 2017)
The objective of this study was to evaluate the potential of chitosan in inducing resistance against damping off in tomato caused by Rhizoctonia solani. The tomato seeds were submerged in solution with chitosan for 20 minutes in concentrations of 0.25%; 0.5%; 1% and 2% and in the control (distilled water only). The seeds were sown in polystyrene trays containing substrate inoculated with R. solani and kept in a growth chamber with 12 hours photoperiod and temperature of 25 ± 2 ºC for 14 days. After this period we evaluated the survival of seedlings, length and fresh weight and activity of the enzyme phenylalanine ammonia lyase (PAL), chitinase and β-1.3-glucanase. The results showed that chitosan when applied on tomato seeds at concentration of 0.30% incresead the survival of seedlings growing in substrate inoculated with the pathogen. This result is mainly related to the activation of resistance mechanisms in the plant, evidenced by activation of PAL, chitinases and β-1.3-glucanases enzymes.